Transboundary franchising agreement as an institute of international private law in Russia and Germany: concept and content - E. A. Demicheva (Путеводитель предпринимателя)
The article provides a comparative analysis of a transboundary franchising agreement essential terms in a contects of its implementation in Russia and Germany. The theoretical reflection of the phenomenon of franchising’ essence. The basic features of a notion of transboundary franchising agreement as economic-and-legal category which determine the complex modern trends shaping the concept of transboundary franchising agreement as an institution of international private law. The study made a number of fundamental conclusions and proposals including on recommendations to potential participants of franchising agreements.